Actualization of The Election Supervision Institutions Role in The Recondition of The Post Dynamics of Dispute Dynamics 2019 - Rima Cantika Cahyaningrum (Universitas Muhammadiyah Surakarta, 2020)
This article aims to analyze the impact of the dynamics of the 2019 General Election (Pemilu) dispute and provide an idea of restoring the image of the election in society after the contestation conflicts that have occurred. The method used in this research is descriptive method to present a complete overview of the social setting for exploration and clarification of a social phenomenon or reality. In this case, this is a negative overview because of the 2019 election dispute, by describing a number of variables with respect to the problem and the unit studied between the phenomena being tested. The results of the research show that the holding of elections as one of the steps in realizing a democratic state has become a chaotic political event because some of the methods taken by election participants are to discredit other participants to get votes. This method not only brings a bad overview not only to the participants, but also to the implementation of elections that can result in disruption of security and stability in the condition of society in Indonesia. The novelty of this research is the need to optimize the role of the election supervisory institution as one of the election organizers to improve a good overview of democracy